O Programa Nacional de Alimentação Escolar (PNAE) na rede municipal de Fortaleza: uma avaliação em profundidade das práticas sustentáveis na percepção dos atores sociais - Moreira, Adriana Duarte dos Santos (2024)
Throughout the history of Brazilian education, school meals, a program started in Brazil in 1955, underwent significant changes through the National School Meal Program (PNAE). This fact resulted in an increase in the acquisition of family farming products in the municipality of Fortaleza. Currently, this context motivated the research of this work, with the general objective of evaluating the perception of the social actors involved in the context of the PNAE, identifying sustainable practices in terms of what is carried out properly and what needs to be improved and as specific objectives: understanding the functioning of the PNAE, identifying the weaknesses and strengths of a technical nature and the political context, relating the factors that contribute to and hinder family farming in the municipality, analyzing the implementation (or not) of the PNAE's proposed objectives regarding the efficiency and effectiveness of the policy public purchasing process and identify how social actors participate in the program and their perceptions about sustainability. Therefore, we opted for documentary research with a qualitative approach, based on In-Depth Assessment (Rodrigues, 2008, 2011). The Program's guiding documents, public calls and electronic auctions, reports and menus from the Municipal Secretariat of Fortaleza were analyzed. As data collection strategies, semi-structured interviews and observation were used. The field research involved, in total, 12 social actors who work directly with the PNAE. The qualitative data, originating from field collection, were analyzed using Content Analysis (Bardin, 2011). To analyze the dynamics of the process, we highlight Costa (2013), Lopes (2014) and Sambuiche et al. (2012). Regarding the implementation (or not) of the proposed objectives of the PNAE, we resorted to the works of Arretche (2001), Wanderley (2011) and Salgado et al. (2015). In investigating how social actors participate from the perspective of sustainability, we highlight Moraes (2014), Bezerra (2018) and Melgaço (2021). We note that, despite being an effective public policy, it presents major challenges in terms of promoting sustainable development and the commercialization conditions of family farming, requiring greater financial investment in which the per capita has annual correction as well as the training of social actors in the program, since Fortaleza is the fourth largest network and the first capital in the Northeast region in terms of number of enrolled students.